Use of the circular training method in section classes during distance education - Nazarenko, I. (Problems of Engineer-Pedagogical Education, 2023)
This article examines the expediency of using the circular method of training in sectional classes during distance learning. The scientific and methodological literature on this topic was studied and analyzed, and the relevance of conducting this research was established. The teaching of physical education in institutions of higher education is adapted to the modern conditions of martial law, therefore teachers face a difficult task, which is to maintain the level of physical fitness of students, motivate them to do independent work, and improve their psycho-emotional state. During the global pandemic and hostilities, the level of physical fitness of modern youth has decreased. This is evidenced by the latest scientific research, so there is a problem in eliminating these consequences. In the study, the initial level of physical fitness of students was determined and compared with the final indicators. Complexes of physical exercises were developed, under the influence of which there were changes in the physical development of students. Charts showing positive percentage changes are shown. The results of a comparative analysis of the indicators of physical fitness of students of Ukrainian Engineering Pedagogics Academy are presented, which allow claiming that, under the influence of circular training, physical fitness and strength indicators improve, along with the improved performance of control tests. Carrying out sets of physical exercises using the circular training method not only improves physical qualities, but also has a positive psychological effect, reduces stress and helps fight depression. Nowadays, it is becoming especially relevant.